Debating the global financial architecture - Armijo, Leslie Elliott (Albany : State University of New York Press, 2002)
Political scientists and economists set out their disparate views on what global financial structure would best promote world economic growth and therefore political stability. Most are American academics, but some are policy makers and advisors, and some are from other countries. Most of the 10 studies were last revised in 2000. Annotation copyrighted by Book News, Inc., Portland, OR.
The terms of the debate: what's democracy got to do with it? / Leslie Elliott Armijo -- Global financial architecture and hegemonic leadership in the new millennium / Mark R. Brawley -- Capital controls: why do governments hesitate? / Benjamin J. Cohen -- Reforming the international financial institutions: dueling experts in the United States / C. Fred Bergsten -- The economic case against free capital mobility / David Feliz -- The redesign of the international financial architecture from a Latin American perspective: who pays the bill? / Eduardo Fernández-Arias and Ricardo Hausmann -- Reform proposals from developing Asia: finding a win-win strategy / Ashima Goyal -- Japan and the new financial order in East Asia: from competition to cooperation / Henry Laurence -- Reform without representation? The international and transnational dialogue on the global financial architecture / Tony Porter and Duncan Wood -- The European Monetary Union as a response to globalization / Erik Jones -- Of bubbles and buildings: financial architecture in a liberal democratic era / Lawrence Whitehead.
Includes index.
Print version record.
Includes bibliographical references and index.
English.
JSTOR
Keywords: International finance; BUSINESS & ECONOMICS -- Finance; International finance